PENGEMBANGAN MEDIA PEMBELAJARAN LABORATORIUM BERBASIS DIGITAL “TARS” PADA MATERI LITOSFER DALAM MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK SMA NEGERI 16 SURABAYA - Lestary, Tika Chandrika; Rindawati, Rindawati; Widodo, Bambang Sigit (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This study aims to develop a digital laboratory-based learning media called “Terra Academy Rock and Soil” (TARS) and evaluate its effectiveness on student activeness and learning outcomes. The research used the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model and was conducted at SMA Negeri 16 Surabaya involving 70 grade X students, divided into experimental and control classes. The use of the TARS digital laboratory in the experimental class resulted in an increase in the average learning outcomes from pretest (71) to posttest (76). Meanwhile, the control class only showed an increase from the average pretest (71) to posttest (72). Based on the results of the independent sample t test in the experimental class, the sig (2-tailed) value of 0.042 <0.05 was obtained, so it can be concluded that there is a significant difference between the average learning outcomes of students in the control and experimental groups, proving that TARS has a more positive impact on student learning outcomes. Although effective, this development has limitations, namely not supporting device types with the IOS operating system, so it needs to be developed further. ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis laboratorium digital bernama